Integration of Chinese and Russian stock markets with world markets: National and sectoral Perspectives - Jan Babecký; Lubos Komárek; Zlatuse Komárková (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
Interest in examining the financial linkages of economies has increased in the wake of the 2008/2009 global financial crisis. Applying the concepts of beta- and sigma-convergence of stock market returns, we assess changes over time in the degree of stock market integration between Russia and China as well as between them and the United States, the euro area and Japan. Our analysis is based on national and sectoral data spanning the period September 1995 to October 2010. Overall, we find evidence for gradually increasing stock market integration after the 1997 Asian financial crisis and the 1998 Russian financial cri-sis. Following a major disruption caused by the 2008/2009 global financial crisis, the process of stock market integration resumes between Russia and China, and with world markets. Notably, the episode of sigma-divergence from the 2008/2009 crisis is stronger for China than Russia. We also find that the process of stock market integration and the impact of the recent crisis have not been uniform at the sectoral level, suggesting potential for d-versification of risk across sectors.
URN:NBN:fi:bof-201408072085
Keywords: C23; G15; G12; 330; Stock market integration; beta-convergence; sigma-convergence; China; Russia; sectoral and national analysis